The association between inflammatory and immune system biomarkers and the dietary inflammatory index in patients with COVID-19 - Barania Adabi, Somayyeh; Daneghian, Sevana; Khalkhali, Hamidreaza; Nejadrahim, Rahim; Shivappa, Nitin (Frontiers in Nutrition, 2023)
Background: Inflammation and cytokine storm have been reported to be the main cause of acute symptoms of coronavirus disease (COVID-19). Diet-induced inflammation may affect the condition of patients with COVID-19. Therefore, this study aimed to investigate the relationship between disease severity, inflammatory and the immune system biomarkers with the dietary inflammatory index (DII) in patients with COVID-19. Methods: This cross-sectional study was conducted on 500 adult patients with COVID-19. Patients were divided into mild, moderate and severe conditions based on clinical and laboratory evidence. Valid food frequency questionnaire (FFQ) was used to determine DII and E-DII scores. Serum CRP level and blood cell count were measured for all patients. Results: COVID-19 patients with higher DII had higher consumption of fat and carbohydrate and lower intakes of protein, anti-inflammatory nutrients, garlic, caffeine, tea, onion, and fiber (P<0.05). Higher levels of DII were significantly associated with higher CRP, neutrophil percent, and neutrophil-lymphocyte ratio (NLR) and lower lymphocyte percent (P<0.05). Median day of hospitalization in COVID-19 patients with higher DII was higher compared to the patients with lower DII (7 vs. 1 days, P<0.05). Conclusion: There is a positive correlation between DII and inflammation, immune hyperactivation and length of hospital stay in COVID-19 patients. Further longitudinal studies are necessary.